Ubiquitous Chromatin Modifiers in Congenital Retinal Diseases: Implications for Disease Modeling and Regenerative Medicine - Basinski, Brian W.; Balikov, Daniel A.; Aksu, Michael; Li, Qiang; Rao, Rajesh C. (Trends in molecular medicine, 2021)
Retinal congenital malformations known as microphthalmia, anophthalmia, and coloboma (MAC) are associated with alterations in genes encoding epigenetic proteins that modify chromatin. We review newly discovered functions of such chromatin modifiers in retinal development and discuss the role of epigenetics in MAC in humans and animal models. Further, we highlight how advances in epigenomic technologies provide foundational and regenerative medicine-related insights into blinding disorders. Combining knowledge of epigenetics and pluripotent stem cells (PSCs) is a promising avenue because epigenetic factors cooperate with eye field transcription factors (EFTFs) to direct PSC fate – a foundation for congenital retinal disease modeling and cell therapy. Surprisingly, many ubiquitous chromatin-modifying regulators control retinal development. They are linked to congenital blinding diseases such as microphthalmia.Disruption of retinal cell fate occurs via alterations in the catalytic activity of chromatin modifiers, inactivation of non-catalytic cofactors that comprise non-canonical epigenetic complexes, and temporal dysregulation of protein–transcription factor (TF) interactions that engage chromatin.Advances in PSC-derived retinal organoids and epigenomic technologies have enabled a deeper understanding of the causal role of chromatin accessibility and modifications, and of non-coding regions of the genome, in microphthalmia.Such advances provide translational insights into the roles of epigenetic memory and TF (e.g., TP53) mutations in source PSCs used for cell therapies in age-related blinding diseases.